BIODIVERSITY AND ASSESSEMENT AND CONSERVATION STATUS FOR SUSTAINING AVIFAUNA IN REGION OF SOUK AHARS - TAR ZINEDDINE CHARGUI; BENSLIM CHAIMA (My University, 2024)
The aim of thisresearchis to gain a betterunderstanding of the composition, distribution, and conservation status of birdspecies in thisspecific area by conductingcomprehensivefieldsurveys, data collection, and ecologicalanalysis. Our goal is to contribute to bothregionalecologicalknowledge and broader efforts in sustainingbiodiversity by highlighting the avifauna of Souk Ahras and developing conservation strategies. Our study habitats were frequented by a very large number of species recorded during our 336 visits (336 IPA), a total of 5429 pairs of birds in 14 ordres, 39 family and 102 species , 61 bird species were found in forest stands , 41 in Afforested stands and 86 in Riparian forests. ---------------------------------------------------------------------------------------------------------------------------------------- الهدف من هذا البحث هو اكتساب فهم أفضل لتكوين وتوزيع وحالة حفاظ أنواع الطيور في هذا المجال المحدد من خلال إجراء مسوحات ميدانية شاملة وجمع البيانات والتحليل الإيكولوجي. هدفنا هو المساهمة في المعرفة البيئية الإقليمية والجهود الأوسع لدعم التنوع البيولوجي من خلال تسليط الضوء على طيور سوق أهراس وتطوير استراتيجيات الحفاظ.كانيترددعلىموائلدراستناعددكبيرجدًامنالأنواعالمسجلةخلالزياراتناالبالغعددها336 ، 5429 زوجًامنالطيورفي 14 رتبة،و 39 عائلةو 102 نوعًا،و 61 نوعًامنالطيورتمالعثورعليهافيالغابات، 41 فيالغاباتالاصطناعية و 86 فيالغاباتالنهرية. -------------------------------------------------------------------------------------------------------------------------------------------- L’objectif de cette recherche est d’acquérir une meilleure compréhension de la composition, de la répartition des espèces avifaunistiques forestières et de leur état de conservation en s’appuyant sur la méthode des IPA et l’analyse synécologique non paramétrique. Les habitats de notre étude ont été fréquentés par un très grand nombre d’espèces enregistrées lors de nos 336 visites (336 IPA), un total de 5429 couples d’oiseaux dans 14 ordres, 39 familles et 102 espèces , 61 espèces d’oiseaux ont été trouvés dans des peuplements forestiers , 41 dans des forêts artificiel et 86 dans des forêts riveraines.